Mittens and Booties Syndrome: A Unique Manifestation of Human Parechovirus Infection in Infants. Issue 9 (September 2019) - Ristagno, Elizabeth H.; Marshall, Gary S.
Abstract : We describe the first 2 cases from the United States, of human parechovirus infection in infants manifesting a distinct rash of the hands and feet. We propose the term "Mittens and Booties Syndrome" and provide a review of the literature of all published cases.